Penanggulangan Kepasiran Dengan Gravel Pack Berdasarkan Sieve Analysis di Sumur A-140, Lapangan X - Deny Fatryanto Edyzoh; M. Nur Mukmin; R. Bambang Wicaksono; Engeline Marlin; Abdul Gafar Karim; Darmiyati, Iin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2022)
This study focuses on analyzing sand grain size distribution from Well A-140 using sieve analysis to determine the optimal gravel pack size for sand control. A series of sieves with varying mesh sizes were used to separate the sand particles, and the cumulative weight of each fraction was converted into a percentage based on the total sample weight of 54.437 grams. The results revealed a relatively uniform grain size distribution, indicated by a sorting coefficient of 2.0625, classified as "well-sorted" according to standard sedimentological criteria. The median grain diameter (D50) obtained from the grain size distribution curve was approximately 0.0098 inches. Based on this value, the recommended gravel pack size is 40/60 mesh, with a screen gauge size of 0.008 inches. These findings provide practical insights for designing an effective gravel pack to reduce sand production, enhance well integrity, and maintain stable oil and gas production performance.